BRINE-MINERAL REACTIONS IN EVAPORITE BASINS: IMPLICATIONS FOR THE COMPOSITION OF ANCIENT OCEANS - Ayora C.; Cendón D.I.; Taberner C.; Pueyo J.J. (My University, 2001)
The chemical evolution of several European Mesozoic and Tertiary evaporite basins was reconstructed by using mineral associations, primary fluid-inclusion analyses, and numerical simulations of evaporation scenarios. The solute proportion recorded in the fluid inclusions can be explained by the evaporation of present-day seawater as a major recharge. The sulfate depletion in the brines is responsible for the type of potash deposit formed, potassium-magnessium sulfates or sylvite. This sulfate depletion can be due either to dolomitization or to the addition of a CaCl2-rich solution to the basin. The sulfate depletion occurred in varying intensity in basins of the same age, as well as throughout the evolution of the same basin. Therefore, changes in potash mineralogy and sulfate depletion in fluid inclusions are not conclusive arguments in favor of secular variations in the composition of the ocean, as recently proposed by several authors.
Keywords: evaporites; potash; ﬂuid inclusions; brines; paleooceanography